Vibration-based damage identification of an unreinforced masonry house model. Issue 3 (March 2017) - Oyarzo-Vera, Claudio; Ingham, Jason; Chouw, Nawawi
Non-destructive vibration-based damage identification techniques are especially attractive for assessing damage in structures of high historical and architectural value. So far, most studies have focused on slender structures built using relatively homogeneous materials. In this study, global damage identification methods based on vibration response parameters were applied for identifying damage in an unreinforced masonry full-scale house model (non-homogeneous material and non-slender structure). The house model was dynamically loaded using an eccentric-mass shaker. Structural damage to the walls was initiated by increasing the amplitude of the applied load. At each damage state, a modal test was performed by impacting the walls with a calibrated hammer. Statistically significant variations of modal frequencies and the modal assurance criteria were considered as suitable parameters to identify damage. It was concluded that different sets of modes can be found for different states of damage because of material degradation, change in the support and connectivity conditions, and breaks in the members continuity generated by damage. All these changes are reflected in variations of modal frequencies and modal assurance criteria. It was also established that prior to identifying the damage distribution on the entire building, it was necessary to determine how the modal frequencies were related to each wall.